THE APPLICATION OF QURANIC INTERPRETATION, THE SUNNA AND IJTIHAD AS THE SOURCE OF ISLAMIC LAW - Prawitra Thalib; Faizal Kurniawan; Mohamad Nur Kholiq (RechtIdee, 2020)
The understanding of Islamic law can not be separated from the interpretation sourced from the Quran, Sunnah and Ijtihad, which later evolved into a flexible and dynamic source of Islamic law following the demands of the times. Although it has flexible and dynamic properties but the interpretation must still maintain the basic principles that remain will never change. This is very important because misunderstand the intent expressed in the Quran and Sunnah will affect the error of understanding the Islamic law itself, therefore it is important to realize that the effort of understanding is not separated from The true interpretation of the will of Allah and the Prophet Muhammad that is contained in the Quran and Sunnah. This paper seeks to introduce the foundation of the pursuits that come from the Quran, Sunnah and Ijtihad, which is done using the method of normative assessment of various references discussing the source of Islamic law. Therefore, it is expected to find the meeting point between the understanding of the Qur'an, Sunnah and Ijtihad with the effort to interpret the source of Islamic law aimed at realizing the benefit of the people.